50.4k views
3 votes
2m - 3n = 14
M + 3 n = -11

User Mollerhoj
by
4.8k points

2 Answers

3 votes

Answer:

The correct answer is M = 1 and N = -4

Explanation:

In order to solve this system, use the elimination method. To do this, simply add the two equations together.

2m - 3n = 14

m + 3n = -11

-------------------

3m = 3

Now solve for m.

3m = 3

m = 1

Now that we have the value of m, we can use either equation to find the value of n.

2m - 3n = 14

2(1) - 3n = 14

2 - 3n = 14

-3n = 12

n = -4

User Lafras
by
5.0k points
1 vote

Answer:

M=-8 N=-1

Explanation:

To solve for M and n, solve for one variable and substitute into the other equation. Solve and repeat.

M+3n=-11

M=-11-3n

Substitute.

2(-11-3n)-3n=14

-22-33n-3n=14

-22-36n=14

-22+22-36n=14+22

-36n=36

n=-1

Now take, n=-1 and substitute into an equation.

M+3(-1)=-11

M-3=-11

M=-8


User Jorge Frias
by
5.3k points